The Provision of Careers Guidance in Welsh Schools - Davies, Rhys; Yunus, Suhaer (International Journal of Population Data Science, 2018)
Background and Objectives Careers guidance for young people is regarded as important for supporting positive labour market outcomes. In particular, by helping young people to develop their career management competencies and their roles as learners and workers, careers guidance can help reduce the number of young people who fall outside of the education, training or employment system and from becoming ‘NEETS’. While the practice of career guidance implicitly reflects a commitment to social equality, there are concerns that the provision of career services may not be taken up by those with the greatest need. Previous research suggests that higher achieving pupils are more likely to receive careers guidance interventions (Anderson et al. 2004), while learners from under-privileged and ethnic minority backgrounds may have relatively limited access to educational, vocational and employment information (Liu and Middleton; 1995; Brown et al. 1991; Watson and Stead, 1990). This paper examines these issues in the context of the provision of careers advice to school pupils in Wales. Methods Data from the Welsh National Pupil Database is combined with client information held by Careers Wales to examine the incidence and nature of careers guidance received by children and how their characteristics effect the likelihood of receiving careers-related services. Logistic regression is used to identify factors associated with the likelihood of receiving careers advice within schools. Findings The findings reveal that students receive more careers information, advice and guidance when they are in Year 10. Generally, careers interventions within schools are more likely to be accessed by those students with the greatest need. Conclusions Steps take to enhance educational and career opportunities of pupils in Welsh schools are effective, as students who have the most need for such interventions are receiving the services.